With the square root method, we need to get the equation in the form of
something squared = something else
and then take the square root of each side.
So, first let's divide each side of your equation by 3, to get
(x-4)^2 = 25
Now we can take the square root of each side, and get
(x-4) = 5 and (x-4) = -5
Remember, 5*5=25, but also -5 * -5 = 25, so taking the square root gives us two solutions. Now we solve each of our equations
(x-4) = 5 --> x = 9
(x-4) = -5 --> x = -1
Our two answers are thus x=9 and x=-1. I leave it to you to insert these values back into the original equation and make sure I got it ok! Always double check your work.